2022
DOI: 10.3390/cancers14215257
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Interplay between Human Oncoviruses and Telomerase in Cancer Development

Abstract: Human oncoviruses are able to subvert telomerase function in cancer cells through multiple strategies. The activity of the catalytic subunit of telomerase (TERT) is universally enhanced in virus-related cancers. Viral oncoproteins, such as high-risk human papillomavirus (HPV) E6, Epstein–Barr virus (EBV) LMP1, Kaposi’s sarcoma-associated herpesvirus (HHV-8) LANA, hepatitis B virus (HBV) HBVx, hepatitis C virus (HCV) core protein and human T-cell leukemia virus-1 (HTLV-1) Tax protein, interact with regulatory e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 169 publications
0
5
0
Order By: Relevance
“…Finally, telomere dysfunction-driven polyploidization is a universal source of tumor evolution that occurs continuously during neoplastic cell growth [ 94 ]. Oncoviruses deregulate telomerase activity and telomere length and promote cancer development [ 95 ]. Interestingly, HCMV activates telomerase [ 96 ], and favors the appearance of PGCCs which are considered as hallmarks of oncoviruses [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, telomere dysfunction-driven polyploidization is a universal source of tumor evolution that occurs continuously during neoplastic cell growth [ 94 ]. Oncoviruses deregulate telomerase activity and telomere length and promote cancer development [ 95 ]. Interestingly, HCMV activates telomerase [ 96 ], and favors the appearance of PGCCs which are considered as hallmarks of oncoviruses [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests potential for new therapeutic approaches, such as using TERT inhibitors, in the treatment of EBV-related cancers. 6,114 Given the important role of TERT in the pathogenesis and progression of viralassociated cancers, targeting TERT has been proposed as a potential therapeutic strategy for these cancers. 115 Several studies have shown that inhibition of TERT expression or activity can reduce cell proliferation and induce apoptosis in HPVassociated cervical cancer cells 116 and EBV-associated nasopharyngeal carcinoma cells.…”
Section: Tert and Terc In Cervical Cancermentioning
confidence: 99%
“…Notably, the inhibition of TERT in Burkitt's lymphomas and LCLs that are EBV‐positive increased the effectiveness of antiviral therapy in inducing apoptosis. This suggests potential for new therapeutic approaches, such as using TERT inhibitors, in the treatment of EBV‐related cancers 6,114 . Given the important role of TERT in the pathogenesis and progression of viral‐associated cancers, targeting TERT has been proposed as a potential therapeutic strategy for these cancers 115 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, virus-related cancers, which commonly require constitutive expression of viral oncoproteins to sustain cell transformation, are characterized by high levels of telomerase activity. In particular, oncoviral proteins, such as high-risk human papillomavirus (HPV) E6, Epstein-Barr virus (EBV) LMP1, Kaposi’s sarcoma-associated herpesvirus (HHV-8) LANA, hepatitis B virus (HBV) HBx, hepatitis C virus (HCV) core protein and human T-cell leukemia virus-1 (HTLV-1) Tax protein, have been demonstrated to contribute to the transcriptional activation of the TERT gene by interacting with negative regulators of TERT transcription ( Tornesello et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%